Fulfilling The Needs of Diverse Students: Teaching Strategies for EFL Inclusive Classrooms - Jumatul Hidayah; Ruly Morganna (Balai Bahasa Kalimantan Tengah, 2019)
This study aimed at investigating teaching strategies and their implementation in EFL inclusive classrooms at one of the junior high schools in Curup-Bengkulu, Indonesia. To garner credible data as desirable, an instrumental case study was conducted by engaging two EFL teachers selected purposively at that school. Interview and observation were deployed as the techniques of collecting data. This study revealed that the teachers applied four teaching strategies ranging from active learning, peer-tutoring, cooperative learning, to direct instruction. Despite many more inclusive teaching strategies which were left aside, the limited extent of inclusion-related pedagogical knowledge and experiences, inadequate reflective teaching, and limited facilities and infrastructure promoting inclusive education, the EFL teachers had been able to implement the aforesaid strategies properly. They had demonstrated that they were sufficiently skillful at the detailed procedures of the implementation of the four strategies in the EFL inclusive classrooms. Further studies are expected to address the application of more instructional strategies for inclusive classrooms such as those suggested by Lawrence-Brown (2004). Revealing both qualitative and experimental data associated with those instructional strategies will be very contributive and meaningful.AbstrakPenelitian ini bertujuan untuk menginvestigasi strategi pengajaran serta penerapannya dalam pembelajaran bahasa Inggris di kelas inklusif di salah satu SMP di Curup, Provinsi Bengkulu, Indonesia. Demi mendapatkan data yang kredibel, studi kasus instrumental dilakukan dengan melibatkan dua orang guru bahasa Inggris yang mengajar di sekolah tersebut. Wawancara dan observasi digunakan sebagai teknik pengumpulan data. Penelitian ini mengungkap bahwa guru tersebut menerapkan empat jenis strategi pengajaran, yaitu active learning, peer-tutoring, cooperative learning, dan direct instruction. Meskipun masih banyak lagi strategi pengajaran yang belum diterapkan, terbatasnya pengetahuan dan pengalaman paedagogik terkait pendidikan inklusif, belum dilakukannya pengajaran reflektif, serta fasilitas dan insfrastrukur pendukung pendidikan inklusif yang terbatas, dua orang guru bahasa Inggris tersebut sudah mampu menerapkan keempat strategi pengajaran tadi dengan baik. Mereka sudah menunjukkan bahwa mereka cukup andal dalam menjalankan prosedur secara detail ketika menerapkan keempat jenis strategi pengajaran tersebut dalam kelas inklusif. Penelitian selanjutnya diharapkan untuk berorientasi pada penerapan berbagai strategi pengajaran inklusif lainnya sebagaimana yang disarankan oleh Lawrence-Brown (2004). Mengungkap data kualitatif serta data eksperimen terkait berbagai strategi pengajaran tersebut akan sangat kontributif dan bermanfaat.